Association between antiretroviral therapy and dental caries in children and adolescents with HIV: a systematic review and meta-analysis - Rubén Aguirre-Ipenza; Anthony Bautista-Pariona; Yolanda Viguria-Chavez; Alejandro Hector Huapaya-Cabrera; Franz Tito Coronel-Zubiate; Sara Antonieta Luján-Valencia; Elda Amaya-Riveros; Heber Isac Arbildo-Vega (BMC Oral Health)
Abstract Objective To evaluate the evidence regarding the association between antiretroviral therapy and dental caries in children and adolescents with HIV. Methods Searches were conducted in five international databases (PubMed, Scopus, EMBASE, CENTRAL, and LILACS) from the inception of records up to October 2024, including studies that examine the impact of antiretroviral therapy on caries in individuals under 18 years of age. The risk of bias was assessed using the Newcastle–Ottawa Scale. Quantitative synthesis was performed using the inverse variance method or Mantel–Haenszel method, depending on the type of outcome analyzed. Measures of association included odds ratios and mean differences, employing a random-effects model with a 95% confidence interval. Results A total of 585 studies were identified, of which 17 were selected for qualitative review and 15 were included in the meta-analysis. The meta-analysis revealed a significantly higher risk of dental caries in children and adolescents with HIV undergoing antiretroviral therapy compared to those without the virus (odds ratio of 2.11; 95% CI: 1.41–3.17). Subgroup analysis showed a stronger association in case–control studies and for the DMFT index. The certainty of the evidence according to GRADE was rated as very low. Conclusion Despite limited certainty, the results suggest that HIV under antiretroviral therapy is associated with a higher risk of dental caries. It is prudent to interpret these results with caution, considering the methodological limitations of the studies. However, given the possible relevance of this association for public health, it is recommended to consider specific dental care protocols for children and adolescents with HIV, as well as the need for preventive strategies integrated into HIV management.